Identification of Chitinolytic Enzymes in Chitinolyticbacter meiyuanensis and Mechanism of Efficiently Hydrolyzing Chitin to N-Acetyl Glucosamine - Zhang, Alei; Mo, Xiaofang; Zhou, Ning; Wang, Yingying; Wei, Guoguang; Hao, Zhikui; Chen, Kequan (Frontiers in Microbiology, 2020)
Chitinolyticbacter meiyuanensis SYBC-H1, a bacterium capable of hydrolyzing chitin and shrimp shell to N-acetyl glucosamine (GlcNAc) as the only product, was isolated previously. Here, the hydrolysis mechanism of this novel strain toward chitin was investigated. Sequencing and analysis of the complete genome of SYBC-H1 showed that it encodes 32 putatively chitinolytic enzymes including 30 chitinases affiliated with the glycoside hydrolase (GH) families 18 (26) and 19 (4), one GH family 20 β-N-acetylglucosaminidase (NAGase), and one Auxiliary Activities (AA) family 10 lytic polysaccharide monooxygenase (LPMO). However, only eight GH18 chitinases, one AA10 LPMO, and one GH20 NAGase were detected in the culture broth of the strain, according to peptide mass fingerprinting. Of these, genes encoding chitinolytic enzymes including five GH18 chitinases (Cm711, Cm3636, Cm3638, Cm3639, and Cm3769) and one GH20 NAGase (Cm3245) were successfully expressed in active form in Escherichia coli. The hydrolysis of chitinous substrates showed that Cm711, Cm3636, Cm3638, and Cm3769 were endo-chitinases and Cm3639 was exo-chitinase. Moreover, Cm3639 and Cm3769 can convert the GlcNAc dimer and colloidal chitin into GlcNAc, which showed that they also possess NAGase activity. In addition, NAGase Cm3245 possesses a very high exo-acting activity of hydrolyzing GlcNAc dimer. These results suggest that chitinases and NAGase from SYBC-H1 both play important roles in conversion of N-acetyl chitooligosaccharides to GlcNAc, resulting in the accumulation of the final product GlcNAc. To our knowledge, this is the first report of the complete genome sequence and chitinolytic enzyme genes discovery of this strain.